2008
DOI: 10.3382/ps.2007-00355
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Salmonella Typhimurium from Salmonella Enteritidis and other Salmonella Serotypes using Random Amplified Polymorphic DNA Analysis

Abstract: Salmonella enterica ssp. enterica serovar Typhimurium and Salmonella enterica ssp. enterica serovar Enteritidis are the major dominating serotypes of Salmonella in poultry and poultry products. Infection by Salmonella Typhimurium is an important cause of morbidity and mortality in poultry. Rapid differentiation of Salmonella Typhimurium from other Salmonella serotypes including Salmonella Enteritidis can be very crutial for public health and for epidemiologists and for the poultry industry. Ten arbitrarily des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Thus, the three reference strains yielded different band profiles with this primer. This observation agrees with those of McKenna et al (1995) on the differentiation of Ty21a vaccine strain from the rest of Salmonella Typhi isolates using a single arbitrary primer, and those reported by Gürakan et al (2008) on the use of a single RAPD primer as a serotype-specific marker for Salmonella Typhimurium.…”
Section: Resultssupporting
confidence: 93%
“…Thus, the three reference strains yielded different band profiles with this primer. This observation agrees with those of McKenna et al (1995) on the differentiation of Ty21a vaccine strain from the rest of Salmonella Typhi isolates using a single arbitrary primer, and those reported by Gürakan et al (2008) on the use of a single RAPD primer as a serotype-specific marker for Salmonella Typhimurium.…”
Section: Resultssupporting
confidence: 93%
“…While the fatty acids in the OS essential oil generally contains polymorphic compounds, such as thymol and carvacrol, compounds, such as γ-terpinene, P-cymene, and thymoquinene, can also be found depending on the growing area (Lukas et al, 2009) . Some studies have reported that essential fatty acids in OS have antioxidant (Luna et al, 2010;Tavarez et al, 2011), anti-microbial (Mitsch et al, 2004;Gürakan et al, 2008), anti-inflammatory (Yoshino et al, 2006), anti-viral (Pilau et al, 2011), anti-tumoral (El-desoukya et al, 2009Al-kalaldeh et al, 2010), anti-ulcer (Afify et al, 2012), anti-fungal (Manohar et al, 2001), and anti-parasitic (Değerli et al, 2012;Remmal et al, 2013) properties, all of which have positive effects on stock performance (Jang et al, 2007;Tekçe & Gül, 2016).…”
Section: Effects Of Origanum Syriacum Essential Oil On Blood Parametementioning
confidence: 99%
“…Salmonella spp are among the group of bacteria in the family Enterobacteriaceae commonly known as enteric bacteria that live in gastrointestinal tracts of warm-blooded animals [3]. The genus Salmonella comprises about 2,579 serovars [8].…”
Section: Background On Salmonella Spp and Salmonellosismentioning
confidence: 99%
“…Salmonella spp are also responsible for typhoid in human in which an estimated 12-33 million cases of typhoid fever occurs globally each year and mortality rate of 10% to 30% reported in Asia and Africa respectively each year [3]. Specific Salmonella spp which are responsible for typhoid in humans are Salmonella typhi and Salmonella paratyphi A and B [2,3].…”
Section: Background On Salmonella Spp and Salmonellosismentioning
confidence: 99%
See 1 more Smart Citation